PENGARUH PELATIHAN DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DI KANTOR BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN BULUKUMBA - ika fatmawati; Moh Aris Pasigai; Nasrullah Nasrullah (Jurnal Ilmu Manajemen Profitability, 2019)
The test results show that the training tcount, which is 2.678 is greater than t table which is 2.02269 with a significance level of 0.011. Therefore, it can be concluded that there is a significant effect of training on the performance of employees of the Regional Development Planning Agency (BAPPEDA) office in Bulukumba Regency. And the value of the compensation tcount is 2.755, which is greater than t table, which is 2.02269 with a significance level of 0.009. Therefore, it can be concluded that there is a significant effect of training on the performance of employees of the Regional Development Planning Agency (BAPPEDA) office in Bulukumba Regency. Compensation is the dominant variable influencing the performance of employees of the Bulukumba Regional Development Planning Agency (BAPPEDA) office with a Beta (Standardized Coefficient) value of 0.440.